Large shopping centres in Poznań as a source of rainwater recovery and irrigation of urban green areas - Szumigała, Paweł Piotr; Urbański, Piotr; Szumigała, Karolina Olenia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
Large-scale facilities in the city cause the loss of significant amounts of rainwater, greenery and biologically active areas. Remedying this situation requires the implementation of a number of spatial planning demands. Increasing the attractiveness and spatial value of urbanised areas state fundamental importance for meeting the needs of local communities in the era of predicted climate change. The study shows that appropriate management of water recovered from the roofs of large-scale buildings can be used to supply significant areas of urban greenery.